Influence of a single injection of beta carotene and/or vitamin A at weaning on subsequent reproductive performance of sows - Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 956 sows was used to determine the influence of a single injection of beta carotene, vitamin A, or the combination of beta carotene and vitamin A at weaning on subsequent reproductive performance. At weaning, sows were allotted randomly to one of the following four treatments: 1) 5 ml of saline (control); 2) 5 ml of beta carotene (200mg); 3) 2 ml of vitamin A (1,000,000 IV); or 4) 5 ml of beta-carotene and 2 ml of vitamin A. A total of 718 sows farrowed following a normal return to estrus « 30 days) and normal gestation length. The other 238 sows that received the injections were removed from the study for failing to return to estrus within 30 days postweaning, failing to conceive, failing to farrow, and lameness. Farrowing rate ranged from 73.2 to 78.4% (average of 75.1 %), but was not influenced significantly by treatment. Total pigs born, pigs born alive, or pigs born dead were not influenced by the injections. These results are different from previous research, which indicated that an injection of beta carotene or vitamin A increased number of pigs born alive. Number of pigs born alive (10.4) may have been too high on the farms used in this study to detect a significant improvement. Another possibility is that a second injection of beta carotene or vitamin A at breeding may be needed to elicit the increase in litter size.
Keywords: Swine; Sows; Litter size; Vitamin A; Beta carotene